Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae) - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zootaxa, 2014)
A critical and annotated review of published records of the Chrysididae of the Nordic and Baltic countries and the Russian part of Fennoscandia is presented with some taxonomic and faunistic notes. A total of 73 species are listed from the region. Additionally, 17 species are deleted. Three species are recorded for the first time from Denmark, six species from Estonia, one from Finland, eleven from Latvia, four from Norway, one from Sweden and 15 from Russian Fennoscandia. Elampus foveatus and Chrysis pulcherrima are reported for the first time from the Nordic and Baltic countries. Lectotypes are designated for Hedychrum cupreum Dahlbom, 1845, Chrysis zetterstedti Dahlbom, 1845, Chrysis succincta var. chrysoprasina Trautmann, 1927, Chrysis succincta var. virideocincta Trautmann, 1927 and Chrysis succincta var. nordstromi Trautmann, 1927. Information and images of the holotypes of Hedychrum metallicum Dahlbom, 1854, Chrysis succincta var. westerlundi Trautmann, 1927 are given. Chrysis integra Dahlbom, 1829 is found to be a new synonym of Hedychridium ardens (Coquebert, 1801) and Chrysis scintillans Valkeila, 1971 a new synonym of Chrysis solida Haupt, 1957. Chrysis terminata Dahlbom, 1854 is reported for the first time as the valid name for C. ignita Form A sensu Linsenmaier, 1959.